Case reportsEndovascular treatment of PA pseudoaneurysm caused by Swan-Ganz catheter - Rudziński, Piotr N.; Demkow, Marcin; Michałowska, Ilona; Abramczuk, Elżbieta; Szymański, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
The following case report describes a complication of Swan-Ganz catheterization and its endovascular treatment with a single coil. Application of this particular catheter in the pulmonary artery during cardiac surgery may lead to mechanical perforation and creation of an extravascular sac, which is called a pseudoaneurysm. There are different methods that lead to tamponade or closure of the leakage. Interventional cardiology procedures are nowadays the most appropriate way of treatment of Swan-Ganz catheter induced vascular complications.